Antitussive Activity of Herbal Cough Medicine on Guinea Pigs (Cavia porvellus) - Zullies Ikawati; Poppy Firzani Arifin; Severinus Nugraha Krisma Sandy; Raphael Aswin Susilowidodo; Rosalina Wisastra (Majalah Obat Tradisional, 2021)
This study aims to investigate the antitussive activity of herbal cough medicine containing combined herbal extracts of Echinacea purpurea, Sambucus nigra (Black Elderberry), Glycyrrhiza glabra (licorice), Vitex trifolia (Indian wild pepper), and Zingiber officinale (ginger). Antitussive assays were conducted on male Dunkin-Hartley albino guinea pigs (Cavia cobaya), which are divided into 5 groups, each with 8 individuals. These 5 groups were assigned for negative control group (treated with CMC-Na 0.5%), a positive control group (treated with Dextromethorphan 20 mg/kg BW), and three groups receiving herbal medicine with 3 different doses (Group I: 145 mg/kg BW, Group II: 290 mg/kg BW; Group III:  580 mg/kg BW, respectively). The antitussive activity was evaluated by using a citric acid-induced cough assay. For baseline level, 20 % m/v liquid citric acid was exposed using a nebulizer for 10 min, then the number of coughs in 15 min was counted.  Sixty (60) minutes after oral administration of the tested herbal cough medicine, the number of citric acid-induced coughs was counted again to see the effect of herbal cough medicine to reduce cough. The number of coughs before and after herbal administration was calculated to obtain antitussive activity, represented by the percentage of cough suppression (PCS). Average PCS for each treatment group is then compared to control positive Dextromethorphan 20 mg/kg BW and control negative CMC-Na 0.5%. Data are analyzed by applying the one-way ANOVA method, which is followed by conducting a Tukey’s Test to discover differences between groups at 95% level of confidence. In terms of the percentage of cough suppression (PCS), treatment doses at 145mg/kg BW, 290 mg/kg BW and 580 mg/kg BW result in 58.48% ± 8.60% (Group I); 58.69% ± 7.96% (Group II); 59.21% ± 8.79% (Group III) PCS, respectively, which insignificantly differ to treatment with Dextromethorphan dose (66.99% ± 9.63 with p > 0.05, implicating that the herbal cough medicine has comparable effect with dextromethorphan in the doses used in this study.